Internationalisation of SMEs: European comparative studies. (16th April 2007) - Ratten, Vanessa; Dana, Leo-Paul; Han, Mary; Welpe, Isabell
We examine new research on the internationalisation of Small and Medium-sized Enterprises (SMEs) in 27 European countries. We find that, in both established market economies and in transition economies, SME international entrepreneurship is driven by internal resources and capabilities, membership in networks or clusters, favourable government policies, economy, competitive market conditions, and industry structure. We then develop a conceptual model and propositions of the drivers of European SME internationalisation. Our findings have important implications for managers in improving their firms' international market performance.